The Form of Muamalah Value Integration in the Independent Curriculum at Muhammadiyah 05 Muara Aman Junior High School - Nuryana, Nana; Febriana, Lety; Firmasari, Desi; Novriadi, Dedy (-, 2025)
This study aims to describe the forms of integration of muamalah values in the implementation of the Merdeka Curriculum at SMP Muhammadiyah 05 Muara Aman. This research uses a qualitative method with a descriptive approach. Data were collected through observation, in-depth interviews with school principals, Islamic Religious Education teachers, and students, as well as documentation of curriculum documents and learning plans. The data analysis technique used the Miles, Huberman, and Saldana model which includes data reduction, data display, and conclusion drawing/verification. The results showed that the integration of muamalah values in the Merdeka Curriculum is carried out through four main dimensions: (1) integration in the curriculum through the formulation of core competencies and learning objectives that contain values of justice, honesty, responsibility, and cooperation; (2) integration in the learning process through contextual methods that link material with muamalah principles in real life; (3) integration in extracurricular activities such as school bazaars, student organizations, and social programs; and (4) integration in school culture through exemplary behavior of teachers, honest canteens, worship habituation, and a culture of mutual cooperation. This study confirms that the Merdeka Curriculum provides strategic opportunities for Islamic schools to integrate muamalah values more flexibly and contextually, thereby forming students who are not only academically intelligent but also have strong Islamic character.